Effect of analogues of cationic peptides on dentin mineralization markers in odontoblast-like cells - Caiaffa, Karina S. [UNESP]; Basso, Fernanda G. [UNESP]; Santos-Filho, Norival A. [UNESP]; de Souza-Costa, Carlos Alberto [UNESP]; Sakai, Vivien T.; Cilli, Eduardo M. [UNESP]; Duque, Cristiane [UNESP] (Elsevier, 2019)
Objectives: To evaluate the effect of analogues of cationic peptides on the viability and the expression of phenotypic and genotypic markers of dentin mineralization in MDPC-23 odontoblast-like cells. Materials and methods: Cells were exposed to serial dilutions of analogues of cationic peptides hBD-3-1CV and KR-12-a5 compared to peptide LL-37 and their viability was assessed by methyltetrazolium assay. Next, peptides (0.78–62.5 μg/mL) were applied on the MDPC-23 cells for evaluating the total protein (TP) production, alkaline phosphatase (ALP) activity and mineralized nodule deposition. Gene expression of mineralization markers (DSPP and DMP-1) was also determined by quantitative PCR. Results: LL-37 and hBD-3-1CV treatment did not affect cellular viability at concentrations below 62.5 μg/mL. KR-12-a5 reduced cell viability above 31.25 μg/mL. TP production was similar for all groups compared with the control group, except by hBD-3-1CV (at 15.62 μg/mL). LL-37 (at 62.5 μg/mL) induced higher ALP activity than control and other experimental groups. LL-37 and hBD-3-1CV, at 62.5 μg/mL and KR-12-a5 at 31.25 μg/mL stimulated the highest deposition of mineralized nodule. Overall, no statistical differences were observed between the groups for DSPP-1 and DMP-1 expressions. Conclusions: LL-37 was the only peptide that induced both ALP activity and mineralized nodules deposition, without affecting cell viability. None of peptides tested induced the expression of DSPP or DMP-1, genes commonly involved in active dentin mineralization.
Keywords: Cationic antimicrobial peptides; Cell culture; Cytotoxicity; Endodontics; Polymerase chain reaction